1989
DOI: 10.1073/pnas.86.21.8492
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an epitope of the diffuse systemic sclerosis marker antigen DNA topoisomerase I: sequence similarity with retroviral p30gag protein suggests a possible cause for autoimmunity in systemic sclerosis.

Abstract: The possibility that viruses play a role in the etiology of various autoimmune diseases has been proposed. One approach to the search for these agents involves identifying potential crossreactive epitopes in viruses that infect cells of the immune system or of the target tissues. Antibodies to DNA topoisomerase I are the marker autoantibodies for diffuse systemic sclerosis. The major epitope of the antigen was therefore sought through cloning and sequencing of the cDNA for human topoisomerase I and eventually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 27 publications
1
44
1
3
Order By: Relevance
“…A recent study that maps one epitope recognized by certain sera containing anti-top0 I autoantibodies has confirmed the prediction that the region of topoisomerase I near the active site is recognized by such sera (26). A nonadecapeptide that contains 11 residues from this region of topoisomerase I flanked by 8 residues that are unrelated to topoisomerase 1 was recognized by a panel of 9 patient sera (26).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A recent study that maps one epitope recognized by certain sera containing anti-top0 I autoantibodies has confirmed the prediction that the region of topoisomerase I near the active site is recognized by such sera (26). A nonadecapeptide that contains 11 residues from this region of topoisomerase I flanked by 8 residues that are unrelated to topoisomerase 1 was recognized by a panel of 9 patient sera (26).…”
Section: Discussionmentioning
confidence: 70%
“…A nonadecapeptide that contains 11 residues from this region of topoisomerase I flanked by 8 residues that are unrelated to topoisomerase 1 was recognized by a panel of 9 patient sera (26). Interestingly, this peptide contains a stretch of 6 residues (741-746) that are also found in the p30gag molecule from feline sarcoma virus.…”
Section: Discussionmentioning
confidence: 99%
“…Maul and coworkers (30) suggested that a retroviral agent may be involved in the pathogenesis of SSc, since 6 sequential amino acid residues on top0 I, 741-746, are identical to a sequence present in the group-specific antigen p30gag of some mammalian retroviruses. However, the majority of patient sera recognized multiple epitopes, none of which contain this sequence.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another recent study using oligopeptides, anti-top0 I antibody was found to crossreact with a retroviral protein, p30gag, through 6 amino acid residues commonly possessed by the 2 molecules (18). This may support the role of molecular mimicry in anti-top0 I antibody production.…”
mentioning
confidence: 82%